(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In modern sources, non-alcoholic steatohepatitis is presented as fatty hepatosis, correctly reflecting its pathogenetic essence, and it is emphasised as an increasingly widespread disease. The disease is mainly caused by poor diet and lack of physical activity. Also, diabetes, hormonal disorders and genetic diseases, as well as all risk factors of cardiovascular diseases (arterial hypertension, alcohol consumption, smoking, mental stress, less than normal consumption of fruit and vegetable products, age and gender factors, metabolic syndrome, excess body weight, obesity, etc.) are considered to be the initial and/or aggravating causes of the problem of this period - if predictive, preventive or preventive measures are not carried out in time, scientifically based and individualized, this situation will lead to liver inflammation (steatohepatitis) and dysfunction the risk of import remains.